INDONESIAN DEMOCRACY BEYOND 2024: Coalitional Presidentialism, Presidentialization, and Imperial Presidency - Hanan, Djayadi (Department of Government, FISIP, Universitas Padjadjaran, 2025)
During the presidency of Joko Widodo (2014 - 2024), particularly in his second term, Indonesia’s multiparty presidential democracy has witnessed the rise of an